Measuring Quality of Life in Stroke Survivors: Validity and Reliability of the Spanish COOP/WONCA Scale - Trinidad Sentandreu-Mañó; Adrián García-Mollá; Inmaculada Oltra Ferrús; José M. Tomás; José Ricardo Salom Terrádez (Medicina)
Background and Objectives: Strokes significantly impact patients’ quality of life (QoL), affecting physical, cognitive, and social functioning. While health-related quality of life (HRQoL) assessments are essential for patient-centered care and clinical decision-making, many existing tools are limited by cultural biases or practical constraints. The COOP/WONCA charts offer a simple, brief, and validated alternative for functional assessment, yet their psychometric properties in stroke survivors remain underexplored. This study aims to evaluate the validity and reliability of the COOP/WONCA charts in assessing HRQoL among Spanish stroke survivors. Materials and Methods: Structural validity, reliability, and criterion-related validity were studied for COOP/WONCA charts in a sample of 91 stroke survivors, where 39.6% were women and 60.4% were men. Their ages ranged from 44 to 93 years old (M  =  68.84; SD = 9.44). A total of 70% of the strokes had an ischemic origin and 30% were hemorrhagic. To assess dimensionality, three Confirmatory Factor Analyses (CFA) were performed, differentiated by the inclusion of charts. Results: The CFA corroborate the best fitting of single-factor structure six-charts version (χ2 (9) = 8.69, p = 0.465, RMSEA = 0.000, 90% CI [0.000–0.141], CFI = 0.999, SRMR = 0.048). The results of criterion-related validity indicated significant correlation between dimensions of SF-36 and sociodemographic, clinical and physical variables. Cronbach’s alpha was 0.95 for the 9 domains version and 0.93 for the 6 domains version. Conclusions: These findings support that the COOP/WONCA Spanish version is a reliable and valid scale for assessing health-related quality of life among stroke survivors.